Redefining Disability Through the Responses of Non-disabilities In R. J. Palacio’s Wonder - Rahmadany, Amanda Sekar; Haryanti, Rahayu Puji (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
This article raises the issue of disability, which is part of human diversity, although it often receives discriminatory treatment in society. This study aims to first identify the representation of people with disabilities found in Wonder; second, explain how society's response to people with disabilities is depicted in Wonder; and third, explain the implications of representation and response for the redefinition of people with disabilities in the modern era in Wonder. The qualitative method used in this study focuses on examining data in the form of dialogue and narration in Wonder to identify the characters' various responses to individuals with disabilities. The data is then analyzed by referring to Rohwerder's theory of disability models, which includes five models: charity, medical, social, human rights, and interactional, and is also linked to Stuart Hall's Representation Theory (1997). The results showed various types of community responses, including empathy, acceptance, rejection, and discrimination. The responses shown by the characters in Wonder represent the complex social dynamics in addressing the existence of people with disabilities in society. In short, Wonder is not just a novel that tells the struggle of a child with a disability, but also a mirror of cultural and social values that often stigmatize those who are considered different. This study shows that Wonder is not just an ordinary literary work; through the novel, it can open readers’ perspectives to see that people with disabilities are actually equal. Therefore, Wonder exists not only as a personal story but also as an educative platform that triggers non-disabled awareness towards disabilities.